UJI METODE ACT FAST (FACE, ARM, SPEECH, TIME) TERHADAP TINGKAT PENGETAHUAN KELUARGA LANSIA TENTANG TANDA DAN GEJALA STROKE - Dwi Arianto (Jurnal Keperawatan Muhammadiyah, 2016)
Objective: to analyze the effect of Act FAST to family education  level regarding with signs and symptoms of stroke in elderly with high risk of stroke. Methods: Quasy experiment was used in this study. Seventy family with elderly high risk of stroke were participated. Purposive sampling was performed. NHS Act Fast questionnaire was used to collect the data. The validity and reliability value were achieved. Wilcoxon sign rank test was performed.Results: The result found that ACT FAST was effective to enhance the family education level regarding with signs and symptoms’ of stroke in elderly with high risk of stroke (p= 0.000; α 0.05) Conclusion: the act FAST is one of method than can be used to deliver to enhance the elderly family understanding about sign and symptoms of stroke